Studying the Physicochemical Properties and Isolation of Unsaturated Fatty Acids from Edible Oils by GC-MS and Argentated Silica Gel Chromatography - Saber, Salim Najmaldain; Mohamad, Hikmat Ali; Aziz, Madzlan (Iraqi Journal of Science, 2021)
The core objective of this study was to investigate the physicochemical characteristics and fatty acid composition of the oils of sunflower, olive, virgin coconut and ginger oils, as well as the separation of their unsaturated fatty acids. The data indicated a significant variation in physicochemical properties (acid, saponification, ester, and iodine values) among oils. Transesterification process was carried out at a molar ratio of 1:7:0.1 of oil: methanol: KOH. Fatty acid methyl esters of oils were analyzed by infrared (IR) and gas chromatography–mass (GC-MS) spectrometry. Twelve fatty acids were identified, where the major fatty acid of olive oil was found to be oleic acid (89%), whereas those of sunflower and ginger oils were linoleic acid (80.9 %) and (79.3 %), respectively. Sunflower and olive oils were fractionated by 25% silver nitrate-impregnated silica gel column chromatography. By this method, linoleic acid methyl ester from sunflower and oleic acid methyl ester from olive oil were isolated with high purity percentages and yields. This study is significant for the development of food and pharmaceutical products.